Modulation of extracellular Penicillium expansum-driven acidification by Papiliotrema terrestris affects biosynthesis of patulin and has a possible role in biocontrol activity - Palmieri, Davide; Miccoli, Cecilia; Notardonato, Ivan; Avino, Pasquale; Lima, Giuseppe; De Curtis, Filippo; Ianiri, Giuseppe; Castoria, Raffaello (Frontiers in Microbiology, 2022)
The active regulation of extracellular pH is critical for the virulence of fungal pathogens. Penicillium expansum is the causal agent of green-blue mold on stored pome fruits and during its infection process acidifies the host tissues by secreting organic acids. P. expansum is also the main producer of patulin (PAT), a mycotoxin found in pome fruit-based products and that represents a serious health hazard for its potential carcinogenicity. While it is known that PAT biosynthesis in P. expansum is regulated by nutritional factors such as carbon and nitrogen and by the pH, the mechanistic effects of biocontrol on PAT production by P. expansum are not known. In this work, we assessed how optimal and suboptimal concentrations of the biocontrol agent (BCA) Papiliotrema terrestris LS28 affect both extracellular pH and PAT biosynthesis in P. expansum. In wounded apples, the optimal and suboptimal concentrations of the BCA provided almost complete and partial protection from P. expansum infection, respectively, and reduced PAT contamination in both cases. However, the suboptimal concentration of the BCA increased the specific mycotoxigenic activity by P. expansum. In vitro, the rate of PAT biosynthesis was strictly related to the extracellular pH, with the highest amount of PAT detected in the pH range 4–7, whereas only traces were detectable at pH 3. Moreover, both in vitro and in apple wounds the BCA counteracted the extracellular P. expansum-driven acidification maintaining extracellular pH around 4, which is within the pH range that is optimal for PAT biosynthesis. Conversely, in the absence of LS28 the pathogen-driven acidification led to rapidly achieving acidic pH values (<3) that lie outside of the optimal pH range for PAT biosynthesis. Taken together, these results suggest that pH modulation by LS28 is important to counteract the host tissue acidification and, therefore, the virulence of P. expansum. On the other hand, the buffering of P. expansum-driven acidification provided by the BCA increases the specific rate of PAT biosynthesis through the extension of the time interval at which the pH value lies within the optimal range for PAT biosynthesis. Nevertheless, the antagonistic effect provided by the BCA greatly reduced the total amount of PAT.